DETERMINAN KONSISTENSI PEMBAYARAN ZAKAT PROFESI : STUDI KOMPARASI MUZAKI PENERIMA UPAH DAN NON PENERIMA UPAH - Rizkiyani, Nur Fajriyah; Pancawati Hardiningsih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to compare the muzakki who receive wages and muzakki who are non-wage recipients. The sampling technique used was a non-probability sample with purposive sampling. The average value of the accountability perception of the muzakki who receives wages is higher than that of the non-wage recipients, but the average value of transparency, zakat literacy, income, religiosity, trust and interest in paying professional zakat on non-wage recipients is higher. The results showed that there was no significant difference in perceptions of accountability and transparency of zakat institutions between muzakki who were wage recipients and non-wage recipients, there was no significant difference in zakat literacy, income and religiosity of muzakki wage recipients and non-wage recipients, there was no significant difference in trust in zakat institutions and interest in paying professional zakat between muzakki who are wage recipients and non-wage recipients.